How to Enhance the Managementand Quality of Electronic Publications? - Hrabovskyi, Ye.; Szymczyk, K.; Lukianova, V. (My University, 2023)
The electronic publication format has become valuable and easy to access for a modern person. Many readers prefer electronic publications to print ones. Publication houses that want to access more customers and enhance their sales should consider including electronic formats in their product offers. Managing a publishing company requires constant modification and diversification of products. To a large extent, the offer of publications in electronic format has a chance to attract more customers than the traditional printed form. It is primarily about easy access to the searched reading items. The customers can purchase the publication in various electronic formats, e.g., PDF, MOBI, or ePUB format, according to their needs. It does not require going to the library, reading room, stationery store, or waiting for the parcel at the place of residence. The purchased product, paid or free, immediately becomes available after downloading to the appropriate device. It is a very convenient and quick way to get to publications. Therefore, publishing houses should keep up with the times and offer publications in electronic format. However, a number of factors must be taken into account before such a product is created. Often, there is a need to convert the print version of publications into electronic format - a need to convert documents on formats of computer editorial systems in electronic formats. In the paper, the method of changing the orientation of the page of the elevation publication is proposed. Then a set of parameters of the arrangement elements is developed. The algorithm for the automatic change of page orientation of the viewing edition is created. Based on this algorithm, tools have been developed to automatically change the edition page as an appropriate prototype of automation tools (Adobe, USA product) in HTML format using JavaScript programming language (Japan). For the qualitative work of the prototype, the basic rules of the set and layout were analyzed. The designed complex of typical page layouts, in terms of laying elements on the page. An orientation change algorithm with its restrictions has been developed for each typical layout
Keywords: managing page orientation; managing electronic edition; digital publication management; automatic change, algorithm